Kusoke Adventures: Recycling Interactive Game / Yamen Alzeiter and Elin Eliana Abdul Rahim - Alzeiter, Yamen; Abdul Rahim, Elin Eliana (Faculty of Computer and Mathematical Sciences, 2023)
Recycling activities play a crucial role in the society as these activities have impacts on various aspects such as production, health and environment. Although recycling activities have impacts on the environment, the level of awareness among youth and children regarding recycling is still low. To address this issue, this project aims to develop a 2D interactive game. The game will educate the youth and children about recycling, sorting recyclable materials, and teaching them about the importance of safeguarding the environment. Unlike the conventional text-based approaches such as printed flyers, brochures and books, the interactive elements of the 2D game will engage the target audience when playing the game, which eventually foster their understanding and interest in recycling. The game will also include assessment tools to measure the users' knowledge about recycling. The game is developed using Unity engine and C# programming language, and the assets are created using Adobe Illustrator and Asprite.